Serum levels of prostate specific antigen, free PSA, [-2]proPSA, fPSA/tPSA ratio, Prostate Health Index, and glycosylation patterns of free PSA in patients with benign prostatic hyperplasia pharmacotherapy - Jirásko, Michal; Viták, Roman; Pecen, Ladislav; Pinkeová, Andrea; Tkáč, Jan; Bertók, Tomáš; Bergman, Natalie; Kučera, Radek (The Prostate, 2025)
BACKGROUND: The medication used to treat benign prostate hyperplasia (BPH), a common condition in men over 50 years of age, can alter the levels of biomarkers used in prostate cancer detection. Commonly used medications for BPH include alpha-blockers, 5-alpha reductase inhibitors (5-ARIs), and muscarinic antagonists. We studied the impact of these drugs on total prostate-specific antigen (tPSA), free PSA (fPSA), [-2]proPSA, fPSA/tPSA ratio, and the Prostate Health Index (PHI), as well as novel potential biomarkers in the form of glycan composition of fPSA. PATIENTS AND METHODS: Serum samples were collected from 564 males with BPH, with a mean age of 68.5 years. The samples were used to measure levels of tPSA, fPSA, and [-2]proPSA. The fPSA/tPSA and PHI were then calculated. The glycan composition of fPSA was analyzed using lectin-based glycoprofiling. Pharmacotherapy data was collected from the patients' medical records. RESULTS: Alpha-blocker monotherapy was associated with higher fPSA and fPSA/tPSA ratio, and decreased PHI. Levels of tPSA were not impacted. Alpha-blocker and 5-ARI dual therapy was associated with reduced levels of fPSA, [-2]proPSA, and PHI. Therapy combining alpha-blockers and antimuscarinic agents did not significantly influence biomarker levels apart from an increase in a Maackia amurensis lectin-recognized glycan originating in fPSA. CONCLUSION: BPH pharmacotherapy notably affects prostate cancer biomarkers. Recognizing the impact of pharmacotherapy is crucial for achieving an accurate diagnosis of prostate cancer and for planning treatment.
Keywords: Prostatic Neoplasms; alfa blokátory; prostata; nádory prostaty; Humans; hyperplazie prostaty; 5‐alpha reductase inhibitors; lidé středního věku; Aged; Prostate-Specific Antigen; senioři; lidé; PSA; antagonisté muskarinových receptorů; Adrenergic alpha-Antagonists; prostate cancer; Prostatic Hyperplasia; alpha‐blockers; benign prostate hyperplasia; inhibitory 5-alfa-reduktasy; glykosylace; Male; Prostate; Middle Aged; prostatický specifický antigen; Aged, 80 and over; senioři nad 80 let; 5-alpha Reductase Inhibitors; mužské pohlaví; Glycosylation; antimuscarinic agents; Muscarinic Antagonists